ChemInform Abstract: Late‐Stage Deoxyfluorination of Alcohols with PhenoFluor. Issue 30 (4th July 2013) - Sladojevich, Filippo; Arlow, Sophie I.; Tang, Pingping; Ritter, Tobias
Abstract The reaction proceeds considerably faster if less sterically hindered or allylic alcohols are deployed.